Ocenjevanje displazije kolka pri odraslih - Mavčič, Blaž (Medicinski razgledi, 1999)
Degeneration of the articular cartilage and osteoarthritis of the hip joint are most often idiopathic (primary osteoarthritis). In patients with known pathogenesis (secondary osteoarthritis), the disease is most commonly due to mechanical bone deformation, termed hip dysplasia. The treatment is planned onthe basis of clinical, anatomic and biomechanical characteristics of the hipjoint. The biomechanical pattern is most frequently determined by the Wiberg centre-edge angle of lateral covering of the femoral head. Dysplastic hips seem to be characterized by an unfavourable stress distribution to the weightbearing area. A mathematical model is used to find out which geometric parameters in addition to the Wiberg centre-edge may influence the distribution of stress on the weight-bearing surface. The author describes themethod for assessing these parameters from a standard antero-posterior rentgenogram. The procedure was tested on healthy subjects with small centre-edge angles, reporting no clinical problems. We analyzed the mathematical model for determining stresses exerted on the weight-bearing articular surface of the hip during the one-legged stance, and determined the parameters affecting stress distribution in the hip joint for various hip and pelvis configurations. Standard anteroposterior rentgenograms of 411 subjects were examined and the subjects with centre-edge angles smaller than 30 degreeswere selected. The mathematical model was used to determine the values of radial stress for the selected subjects. The following parameters are relevant to the assessment of hip dysplasia: the radius of the sphere that corresponds to the hip weight bearing surface r, the magnitude of the force R,and the parameter termed functional angle of the femoral head covering, which is used here for the first time and equals the sum of the centreedge angle and the angle of (Abstract truncated at 2ooo characters)
Keywords: kolčni sklep; Osteoarthritis, hip; ortopedija; Diagnosis; displazije; Hip dislocation; Biomechanics; biomehanika; modeli; Adult; Weight-bearing; Models, theoretical; Pressure; diagnostika